The fuzzy power flow revisited - Manuel A. Matos (2005)
The idea behind the first proposal of the Fuzzy Power Flow (FPF) was to analyze the impact of the uncertainties in load and generation at the power flow level, when no statistical information is available. Further development of the field addressed the optimal power flow problem and the use of fuzzy methodologies to help planners of the composite generation-transmission system. In a market environment, transmission system adequacy may be defined as the ability of the system to meet reasonable demands for the transmission of electricity. The starting point of this paper is that FPF can be used as a tool to quantify this adequacy, without the need of making too many assumptions about load and generation uncertainties. However, some changes in the basic concept of the FPF are needed in order to accomplish this task - part of the paper is devoted to the description of the adequate formulation. We'll also show that this formulation can be used both in the normal operation situation and in the reliability evaluation of the transmission system. An illustrative example completes the paper.